(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
In this issue, we introduce the Urdimento Editorial Team, including editors, associate editors, thematic dossier editors, editorial board members, and reviewers working on this issue of Urdimento. We also introduce the editorial support team.